1999
DOI: 10.1021/jf981113t
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Theanine, γ-Glutamylethylamide, in Rats

Abstract: The metabolism of theanine, one of the major amino acid components in tea (Camellia sinensis), was studied in rats. High-performance liquid chromatography (HPLC) with fluorometric detection was used to evaluate the nature of theanine's metabolites in plasma, urine, and tissues. In the urine samples collected after administration of 100, 200, and 400 mg each of theanine, intact theanine, L-glutamic acid, and ethylamine, these compounds were detected in a dose-dependent manner. When 200 mg of theanine was orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(67 citation statements)
references
References 24 publications
(22 reference statements)
4
63
0
Order By: Relevance
“…Previously, we detected theanine after intragastrical administration in various rat tissues such as serum, liver and brain (Terashima et al 1999). Some reports suggested that theanine might be degraded via glutamic acid because its structure is similar to glutamic acid, and it was suggested that enzymatic hydrolysis of theanine to glutamic acid and ethylamine was accomplished in the kidney (Unno et al 1999) (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
“…Previously, we detected theanine after intragastrical administration in various rat tissues such as serum, liver and brain (Terashima et al 1999). Some reports suggested that theanine might be degraded via glutamic acid because its structure is similar to glutamic acid, and it was suggested that enzymatic hydrolysis of theanine to glutamic acid and ethylamine was accomplished in the kidney (Unno et al 1999) (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
“…In addition, many animal studies showed that tea flavan-3-ols are able to cross the blood-brain barrier Bastianetto et al, 2005). Previous experiments hold that γ-aminobutyric acid (GABA) and L-theanine are also able to across the blood-brain barrier (Unno et al, 1999;Jäger and Saaby, 2011;da Silva Pinto, 2013).…”
Section: Prevention Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…One example is an amino acid found in tea (theanine) which could act as a neurotransmitter. A study in rats found that theanine modulated serotonin and dopamine levels and appeared to improve memory and learning ability (Unno et al, 1999). Work on humans is needed to confirm this finding.…”
Section: Mood and Mental Performancementioning
confidence: 99%